Methodological aspects of minimal residual disease assessment by flow cytometry in acute lymphoblastic leukemia: A french multicenter study. (1st November 2014) - Fossat, Chantal; Roussel, Mikael; Arnoux, Isabelle; Asnafi, Vahid; Brouzes, Chantal; Garnache‐Ottou, Francine; Jacob, Marie‐Christine; Kuhlein, Emilienne; Macintyre‐Davi, Elizabeth; Plesa, Adriana; Robillard, Nelly; Tkaczuk, Jean; et al.
<x xml:space="preserve">Abstract</x> Background Minimal residual disease (MRD) assessment provides a powerful prognostic factor for therapeutic stratification in acute lymphoblastic leukemia (ALL). Multiparameter flow cytometry (MFC) has the potential for a rapid and sensitive identification of high risk patients. Our group has previously published that MRD levels analyzed by clone specific Ig/TcR‐QPCR and MFC were concordant at a sensitivity of 10−4. Here we report the MFC methodological aspects from this multi‐center experience. Methods MRD was assessed by MFC in 1030 follow‐up samples from 265 pediatric and adult patients with de novo ALL treated in the FRALLE, EORTC, or GRALL clinical trials. MRD assessment as applied by the eight participating MFC laboratories is described in detail regarding cell preparation, leukemia‐associated immunophenotype (LAIP) markers and data analysis. Samples were obtained from bone marrow (BM) and peripheral blood (PB). Immunostaining was performed after erythrocyte lysis or Ficoll enrichment. Results This study confirms the applicability of MFC‐based MRD assessment in 97% of patients with ALL at the 10−4 cut‐off. MRD values after Ficoll enrichment and erythrocyte lysis were found comparable. Higher MRD values were obtained in BM than in PB, especially for B‐lineage ALL. Conclusions Measurement of MRD by MFC at the 10−4 cut‐off is applicable within a few hours for almost all patients and using a comparable analytical strategy allows for multicenter collaborative studies. The method can be introduced in a strategy aimed at defining the risk of failure of patients with childhood or adult ALL. © 2014 International Clinical Cytometry Society